2006
DOI: 10.1186/1475-2840-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Value of serum glycated albumin and high-sensitivity C-reactive protein levels in the prediction of presence of coronary artery disease in patients with type 2 diabetes

Abstract: BackgroundCoronary artery disease (CAD) is a major vascular complication of diabetes mellitus and reveals high mortality. Up to 30% of diabetic patients with myocardial ischemia remain asymptomatic and are associated with worse prognosis compared to non-diabetic counterpart, which warrants routine screening for CAD in diabetic population. The purpose of this study was to evaluate the clinical value of serum glycated albumin and high-sensitivity C-reactive protein (hs-CRP) levels in predicting the presence of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Although the classification of significant CAD as angiographic percent stenosis ≥70% at the site of coronary artery lesions in our study is to some extent arbitrary, this criterion of stenosis severity has been correlated with physiologic significance, has relevance to commonly applied angiographic standards and is widely accepted clinical practice [19]. Consistent with previous reports [6,7], we also show that measurement of serum GA levels was able to ascertain the disparity in the same batch of patients; those with diabetes and higher serum GA levels were more prone to develop severe coronary disease. A GA ≥20% was associated with a 2.69-fold increase in relative risk for significant CAD.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although the classification of significant CAD as angiographic percent stenosis ≥70% at the site of coronary artery lesions in our study is to some extent arbitrary, this criterion of stenosis severity has been correlated with physiologic significance, has relevance to commonly applied angiographic standards and is widely accepted clinical practice [19]. Consistent with previous reports [6,7], we also show that measurement of serum GA levels was able to ascertain the disparity in the same batch of patients; those with diabetes and higher serum GA levels were more prone to develop severe coronary disease. A GA ≥20% was associated with a 2.69-fold increase in relative risk for significant CAD.…”
Section: Discussionsupporting
confidence: 79%
“…Glycated hemoglobin A 1c (HbA 1c ) has been widely recognized as a marker of glycemic control [3] and was used to estimate the degree of coronary artery disease (CAD) and the risk of major adverse cardiac events (MACE) after successful implantation of drug-eluting stents in patients with type 2 diabetes mellitus (T2DM) [4,5]. Glycated albumin (GA) accounts for almost 80% of the circulating glycated proteins in vivo and is related to the development and progression of vascular complications in diabetes [6,7,8,9]. Although both serum GA level and blood HbA 1c concentration are closely associated with systemic inflammation and increase the likelihood of atherosclerosis [10,11], it remains unclear whether they are equally important indicators of severe coronary disease for patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…The linear range for this assay was 3.2-68.1% and the maximum inter-assay coefficient of variation (CV) was < 3.0% [11,12,14]. …”
Section: Methodsmentioning
confidence: 99%
“…These results are supported by previous studies in Chinese populations. [18][19][20] These findings suggest that the combined use of EZ plus atorvastatin resulted in higher lipid-lowering effects than using atorvastatin alone. This could be associated with the restriction of the "cholesterol escape" observed when using statins alone.…”
Section: Discussionmentioning
confidence: 89%
“…These results are supported by previous studies in Chinese populations. [18][19][20] Studies have demonstrated that the coronary artery lesions in patients with ACS and T2DM are more severe than those in patients without T2DM, leading to poorer prognosis. 21) Therefore, aggressive lipid-lowering treatment is recommended for patients with T2DM to control their LDL-C levels.…”
Section: Discussionmentioning
confidence: 99%